The role of CXC-chemokine receptor CXCR2 and suppressor of cytokine signaling-3 (SOCS-3) in renal cell carcinoma - Stofas, Anastasios (BioMed Central, 2014)
BACKGROUND: Chemokine receptor signaling pathways are implicated in the pathobiology of renal cell carcinoma (RCC). However, the clinical relevance of CXCR2 receptor, mediating the effects of all angiogenic chemokines, remains unclear. SOCS (suppressor of cytokine signaling)-3 is a negative regulator of cytokine-driven responses, contributing to interferon-α resistance commonly used to treat advanced RCC with limited information regarding its expression in RCC. METHODS: In this study, CXCR2 and SOCS-3 were immunohistochemically investigated in 118 RCC cases in relation to interleukin (IL)-6 and (IL)-8, their downstream transducer phosphorylated (p-)STAT-3, and VEGF expression, being further correlated with microvascular characteristics, clinicopathological features and survival. In 30 cases relationships with hypoxia-inducible factors, i.e. HIF-1a, p53 and NF-κΒ (p65/RelA) were also examined. Validation of immunohistochemistry and further investigation of downstream transducers, p-JAK2 and p-c-Jun were evaluated by Western immunoblotting in 5 cases. RESULTS: Both CXCR2 and IL-8 were expressed by the neoplastic cells their levels being interrelated. CXCR2 strongly correlated with the levels of HIF-1a, p53 and p65/RelA in the neoplastic cells. Although SOCS-3 was simultaneously expressed with p-STAT-3, its levels tended to show an inverse relationship with p-JAK-2 and p-c-Jun in Western blots and were positively correlated with HIF-1a, p53 and p65/p65/RelA expression. Neither CXCR2 nor SOCS-3 correlated with the extent of microvascular network. IL-8 and CXCR2 expression was associated with high grade, advanced stage and the presence/number of metastases but only CXCR2 adversely affected survival in univariate analysis. Elevated SOCS-3 expression was associated with progression, the presence/number of metastasis and shortened survival in both univariate and multivariate analysis. CONCLUSIONS: Our findings implicate SOCS-3 overexpression in RCC metastasis and biologic aggressiveness advocating its therapeutic targeting. IL-8/CXCR2 signaling also contributes to the metastatic phenotype of RCC cells but appears of lesser prognostic utility. Both CXCR2 and SOCS-3 appear to be related to transcription factors induced under hypoxia.